Implementation of the Numbered Head Together Learning Model Based on Teaching Aids at Mts Panca Dharma Stungkit - Zuhro, Adella Mayza; Sirait, Robin (Lembaga Riset Mutiara Akbar, 2025)
The purpose of this research is to provide a comprehensive explanation of how the Numbered Head Together (NHT) learning model is implemented in the instruction of Panca Dharma Stungkit MT class II students, with a particular emphasis on the subject of Islamic Religious Education.In this study, a qualitative approach is used to evaluate the dynamics of student interactions during the learning process.27 participants were divided into small groups according to the principles of NHT.Content analysis is a research method where the researcher not only examines written documents such as lesson plans and observation sheets but also conducts direct observations and in-depth interviews with teachers and students.The research results show that the Numbered Head Together learning model with teaching aids works well in Islamic religious education.Data shows that students are not only more engaged in the lessons, but they also better understand the material being taught.The structure of the NHT model, which consists of four main stages, supports this success: (1) numbering group members, (2) teacher asking questions, (3) talking and thinking together in groups, and (4) providing answers collaboratively.This phase has proven capable of creating an interactive learning environment and encouraging all students to participate actively.